2017
DOI: 10.1590/2318-0331.0117160452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occurrence of NO3–, Coliform and atrazine in a karst aquifer, Colombo, PR

Abstract: The vulnerability of karst aquifers to contamination by agrochemical compounds was studied. Such contamination occurs due to its geomorphological structure. Despite the fact, aquifers are important to provide potable water, there is a lack of research about karst aquifers in Brazil. The aim of this study was to evaluate the occurrence of nitrates, fecal coliform bacteria and atrazine in shallow and deep wells in the karst aquifer in the State of Paraná, which is affected by agricultural activities. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Rheinheimer et al [28] showed results obtained from groundwater in the Brazilian state of Rio Grande do Sul, had higher concentrations of nitrate, but none exceeding 22 mg L −1 of NO 3 − (5 mg L −1 of N-NO 3 − ). Higher values of nitrate found in shallow wells of Paraná state had maximum of 40.22 mg L −1 of NO 3 − [29].…”
Section: Resultsmentioning
confidence: 82%
“…Rheinheimer et al [28] showed results obtained from groundwater in the Brazilian state of Rio Grande do Sul, had higher concentrations of nitrate, but none exceeding 22 mg L −1 of NO 3 − (5 mg L −1 of N-NO 3 − ). Higher values of nitrate found in shallow wells of Paraná state had maximum of 40.22 mg L −1 of NO 3 − [29].…”
Section: Resultsmentioning
confidence: 82%
“…Many studies have reported concerning herbicide concentrations in aquatic environments [1,2,[8][9][10][11][12][13][14][15] , especially in groundwater, since it is often a direct source of potable water. Groundwater is mainly recharged by rainfall and is an important source of surface water, which moves and spreads along the flow paths of springs, streams, marshes, lakes and ponds.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific research has assessed the presence of pesticides in both surface water and underground water in Brazil (Possavatz et al, 2014;Schelder et al, 2017;Caldas et al, 2019;Guarda et al, 2020;De Deus et al, 2022). Some pesticides excluded from the official list of authorized products were also detected, such as the case of aldrin-dieldrin, chlordane and DDT, which have been forbidden in Brazil since 1985, due to their high carcinogenic potential (Oliveira & Furtado, 2010;Panis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%